2017
DOI: 10.1073/pnas.1701536114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular link between auxin and ROS-mediated polar growth

Abstract: Root hair polar growth is endogenously controlled by auxin and sustained by oscillating levels of reactive oxygen species (ROS). These cells extend several hundred-fold their original size toward signals important for plant survival. Although their final cell size is of fundamental importance, the molecular mechanisms that control it remain largely unknown. Here we show that ROS production is controlled by the transcription factor RSL4, which in turn is transcriptionally regulated by auxin through several auxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
210
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(250 citation statements)
references
References 36 publications
11
210
0
1
Order By: Relevance
“…The crosstalk between auxin and ROS has mainly been reported from studies of plant growth and development (Joo et al , , ). A recent report showed that auxin‐induced ROS production was important for polar root hair growth by inducing the expression of ROS‐generating enzymes (NADPH oxidases) (Mangano et al , ). Auxin signalling could activate RSL4, which directly targets the NADPH oxidases through auxin response factors to modulate ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk between auxin and ROS has mainly been reported from studies of plant growth and development (Joo et al , , ). A recent report showed that auxin‐induced ROS production was important for polar root hair growth by inducing the expression of ROS‐generating enzymes (NADPH oxidases) (Mangano et al , ). Auxin signalling could activate RSL4, which directly targets the NADPH oxidases through auxin response factors to modulate ROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 8, we summarize the relationship between auxin, H 2 O 2 and RCS: auxin imported into the LR founder cells enhances ROS production via RBOH (Ma et al, 2014), which is induced by activation of the transcription factor ROOT HAIR DEFECTIVE 6 LIKE 4 (RSL4) (Mangano et al, 2017). Reactive carbonyl species such as acrolein, crotonaldehyde and HNE, and non-RCS carbonyls, are then produced as a consequence of lipid peroxidation (Biswas and Mano, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, auxin plays an important role in root hair development. Auxin induces RSL4 via different ARFs, including ARF5, ARF7, ARF8, and ARF19 (Mangano et al, 2017;Velasquez et al, 2016). Differences in PIN expression between trichoblast and atrichoblast cells lead to different auxin gradients between cell files and contribute to the site determination of root hair initiation (Balcerowicz et al, 2015).…”
Section: Root Hair Developmentmentioning
confidence: 99%